Pendidikan Anak Nelayan di Desa Eretan Wetan : Pendekatan Berbasis Komunitas untuk Mengatasi Tantangan dan Mendorong Pemberdayaan Masyarakat - Ahmad Ro’i Alfaza; Atikah Syamsi; Tamsik Udin (Concept: Journal of Social Humanities and Education, 2025)
This study examines the educational challenges of fishermen's children in Eretan Wetan Village, focusing on economic factors, accessibility, and cultural views that influence their participation in formal education. The purpose of the study was to identify the barriers faced by fishermen's children in accessing education, and to develop recommendations to improve the quality of education in coastal areas. The method used was qualitative research with a case study approach, where data were collected through in-depth interviews and direct observation of the lives of fishing communities. The results showed that poor socio-economic conditions of families, limited access to education due to the distance of schools, and cultural views that prioritize work as fishermen over formal education, were the main obstacles. Therefore, community-based interventions are needed to overcome these barriers, as well as government policies that support the development of educational infrastructure and increase awareness of the importance of education to empower coastal communities and break the cycle of poverty.